Unmet healthcare needs among the population aged 50+ and their association with health outcomes during the COVID-19 pandemic - Quintal, Carlota Maria Miranda (2023)
The COVID-19 pandemic led to unprecedented levels of subjective unmet healthcare needs (SUN). This study investigates the association between SUN in 2020 and three health outcomes in 2021-mortality, cancer, and self-assessed health (SAH), among adults aged 50 years and older, using data from the regular administration of the Survey of Health, Ageing and Retirement in Europe and from the two special waves administered in 2020 and 2021 regarding COVID-19. Three types of SUN were surveyed: care foregone due to fear of contracting COVID-19, pre-scheduled care postponed, and inability to get medical appointments or treatments demanded. We resort on the relative risk and the logistic specification to investigate the association between SUN and health outcomes. To avoid simultaneity, 1-year lagged SUN variables are used. We found a negative association between SUN and mortality. This result differs from the (scarce) previous evidence, suggesting that health systems prioritised life-threatening conditions, in the pandemic context. In line with previous studies, we obtained a positive association between SUN and worse health, in the case of cancer, though it is statistically significant only for the global measure of SUN (any reason). The higher chances of reporting cancer among those exposed to SUN might mean delayed cancer diagnosis, confirming that healthcare foregone was truly needed for a timely diagnosis. The association between SUN and poor or fair SAH is positive but not statistically significant, for the period analysed.